Here’s looking at the reduction of noninnocent copper corroles via anion induced electron transfer - Ryan Osterloh, W.; Fang, Yuanyuan; Desbois, Nicolas; Naitana, Mario L.; Brandès, Stéphane; Pacquelet, Sandrine; Gros, Claude P.; Kadish, Karl M. (Comptes Rendus. Chimie, 2021)
The synthesis, electrochemical and spectroscopic characterization of five copper triarylcorroles bearing one, two or three meso-nitroaryl substituents is reported. Redox potentials and spectroscopic properties of the neutral Cu(II) corrole cation radicals and singly reduced form of the complexes are reported in $CH_{2}Cl_{2}$ and the ability of the initial noninnocent derivatives to be chemically reduced via anion induced electron transfer (AIET) is explored using cyanide ($CN^{-}$) or fluoride ($F^{-}$) anions in the form of tetra-$n$-butylammonium salts. UV–visible spectra of the singly reduced corroles and the species generated after addition of $CN^{-}$ or $F^{-}$ to solutions of the neutral compounds are identical, thus confirming the AIET event in these systems. This result, when combined with the facile electrochemical reduction, provides strong indirect evidence for the presence of noninnocence in these systems.